2020
DOI: 10.1021/acs.jpcc.0c03963
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Model for Adsorption-Induced Deformation of Mesoporous Materials with Nonconvex Pore Geometry

Abstract: Adsorption of fluids in nanoporous media causes mechanical stresses which result in deformation. This phenomenon is ubiquitous, and its magnitude depends on the pore size and geometry. Adsorption and adsorption-induced deformation are typically modeled in slit-shape or convex (cylindrical or spherical) pores. However, many porous materials are composed of spherical grains, so that the pores are formed by the intergranular spaces between the convex solid surfaces. Here, we present a first theoretical study of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 62 publications
2
21
1
Order By: Relevance
“…Kolesnikov et al [52] have recently demonstrated that a bridged phase leads to significant compressive strain, as observed also experimentally in the present work. However, the deformation amplitude of the sample CN shows the larger (SANS) or similar (dilatometry) strain at p/p 0 ≈ 0.95 as compared to the two activated samples.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Kolesnikov et al [52] have recently demonstrated that a bridged phase leads to significant compressive strain, as observed also experimentally in the present work. However, the deformation amplitude of the sample CN shows the larger (SANS) or similar (dilatometry) strain at p/p 0 ≈ 0.95 as compared to the two activated samples.…”
Section: Discussionsupporting
confidence: 89%
“…For the designated 'bridged phase' the strain recorded in SANS for all three samples increases slightly with relative pressure, but stays in the compressive regime in SANS until relative pressures associated with the filled phase are reached. The slight increase in strain contradicts the recent theoretical results from Kolesnikov et al [52], where the bridged phase leads to increasingly compressive strains only. Although the measured strain is generally compressive in the bridged regime, the clear deviation from the predicted behaviour of SANS strain isotherm demonstrates the necessity to consider other contributions, such as expansive strains originating from microporosity.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations